Individual foraging site fidelity increases from incubation to nestling rearing in a colonial bird. (November 2022) - Ramellini, Samuele; Imperio, Simona; Morinay, Jennifer; De Pascalis, Federico; Catoni, Carlo; Morganti, Michelangelo; Rubolini, Diego; Cecere, Jacopo G.
Abstract : Foraging specialization, whereby animals exploit only a minor fraction of the population's foraging home range or trophic niche, may arise as a response to increasing levels of intraspecific competition. This phenomenon may be particularly frequent in colonial species, when individuals breed in large aggregations and are constrained to exploit shared foraging areas surrounding the colony site where competition for access to food resources may be high. Foraging specialization may be driven by individual foraging site fidelity, occurring whenever individuals consistently target specific foraging sites, which may differ from those used by other colony members. We assessed the extent of foraging specialization in a colonial breeding raptor, the lesser kestrel, Falco naumanni, by estimating the repeatability of foraging movement patterns of 45 GPS-tracked individuals during both incubation and nestling rearing. We found that the consistency of individual movement patterns was generally higher during nestling rearing than during incubation. Nestling-rearing individuals, but not incubating ones, travelled along relatively consistent routes when targeting foraging grounds and tended to target the same foraging areas throughout the tracking period. In colonial birds, and likely in altricial species more generally, an increased individual foraging site fidelity during nestling rearing versus incubation may result from increased energy demands due to frequent nestling provisioning in addition to self-provisioning. By consistently exploiting previously visited foraging sites that are likely to be rewarding, nestling-rearing birds might indeed increase their foraging efficiency, shortening food-searching time and maximizing their foraging effort. In addition, the use of distinct foraging areas may reduce intraspecific competition for food, thus buffering an important cost of coloniality. Highlights: Nestling-rearing lesser kestrels showed high individual foraging site fidelity. Incubating birds were less consistent in foraging movement and commuting routes. Site fidelity likely resulted in optimized foraging effort and food-searching time. Site fidelity may increase foraging efficiency in a high energy-demanding phase. Using distinct foraging sites could also reduce intraspecific competition.